Human-Robot Interaction Force Control of Series Elastic Actuator-Driven Upper Limb Exoskeleton Robot - Sun, Zhongbo; Xu, Changxian; Jin, Long; Pang, Zaixiang; Yu, Junzhi (IEEE transactions on industrial electronics (1982), 2025)
To achieve ideal force control in robots interacting with humans, an accurate and stable actuating system is essential. In this article, a novel series elastic actuator (NSEA) with torsion spring and linear spring is designed to provide pliability and safety for physical human-robot interaction in the upper limb exoskeleton robot (ULER). The Hill-based muscle model predicted human joint torques are utilized to determine the linear spring stiffness of the NSEA that facilitates the ULER to provide the reasonable assistive torque. In addition, a human-robot interaction force control (HRIFC) scheme based on an actuator dynamics model is designed, which enables the NSEA-driven ULER to achieve stability of interactive torque in human-in-charge mode and accurate force tracking in robot-in-charge mode. Theoretical proofs demonstrate the stability of the closed-loop system under the proposed HRIFC scheme. The stability and accuracy of force trajectory tracking for the NSEA-driven ULER are verified through simulations and experiments. The muscle activation of the subjects is obtained, which infers the capability of the NSEA-driven ULER to provide effective assistive forces and maintain normal movement modes. Finally, the torsion spring performance test experiments verify that the NSEA-driven ULER can achieve real-time protection and avoid secondary injuries to the subjects.